A preliminary investigation on the effects of the different concentrations of sodium cyanide on Epinephelus coiodes - Salazar, Aileen Valle; Cordero, Paciente A. (Tacloban City Arts and Sciences Division, University of the Visayas Tacloban College, 1998)
Fish samples exposed to 1 ppm dilution get a mean of 0.0797 part per million cyanide concentration while a mean of 0.0718 ppm CN concentration for the fish samples in the 5 ppm dilution and a zero concentration for the 0.05 ppm exposed fish samples.
Fish samples exposed to the 1 ppm and 5 ppm cyanide solution manifested gasping, convulsions, erected fins and flaring of the epercula, as well as loss of equilibrium, buoyancy and darkening of the skin epithelium. Fish samples in the .05 ppm solution had no apparent ill effects.
Samples of Epinephelus coiodes (lapu-lapu) were collected from Paranas, Western Samar and placed in three 112-liter water tanks The fish samples were exposed to 3 dilutions of cyanide, .05 ppm, 5 ppm, and 1 ppm Sodium cyanide for 12 hours.
Undergraduate thesis (Bachelor of Science in Biology) -- University of the Philippines, Tacloban.